Milk to Ice Cream - Neuenfeldt, Elizabeth; Sabelko, Rebecca (Minneapolis, Minnesota : Bellwether Media, Inc., 2021)
"Relevant images match informative text in this introduction to how milk becomes ice cream. Intended for students in kindergarten through third grade"--
Includes bibliographical references and index.
Keywords: Ice cream, ices, etc. -- Juvenile literature; Dairy products -- Juvenile literature